Problematising the Subject: A Foucauldian Reading of the Film“Vanaprastham” - Raveendran, Navya (International Journal of Psychosocial Rehabilitation, 2020)
One of the most widely used theoretical terminologies to refer to the individual is the term ‘Subject.’ One is hailed as a subject after processing him or her through the normalization procedure of existing discourse. Discourse may assign a number of identities to a person and his/her subjectivity is composed of all these identities along with one’s own limited apprehension of the identity ascribed to him/her. Foucault delineates that a person’s subjectivity is the product of the existing discourse and the individual is interpellated into a subject on par with the existing knowledge and power. The proposed paper, with specific reference to the film Vanaprastham, is an attempt to understand the various discursive means by which an individual forms a sense of subjectivity.Vanaprastham delineates the life of Kunjuttan, a Kathakali artist and Subadra, an aristocratic lady. They fell in love with each other and engage in a physical relationship but later Kunjuttan came to realise that Subadra was in love with his ‘puranic’ (epic) role, Arjuna. As the film progresses their subjectivities seem to be shifting and their activities are, more often, a puzzle for the spectator. The proposed study attempts to enumerate the notion of Foucauldian subjectivity with special reference to the characters of Kunjuttan and Subadra.